Complaint-Based Offenses In Sexual Offenses Under The National Criminal Code: Implications For Victim Protection - Sandi Yoga Pradana; Sri Rahayu Lestari Pade; Juhari; Nining Suningra; Nopiana Mozin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The reform of Indonesia’s national criminal law through the enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) introduces significant changes in the regulation of criminal offenses, particularly within the domain of morality-related crimes. One of the most notable developments is the reclassification of certain offenses into complaint-based crimes, which were previously treated as ordinary offenses. This policy shift is grounded in the intention to better respect individual privacy, human dignity, and the autonomy of victims in deciding whether a case should proceed through legal channels. At the same time, it reflects the state’s effort to limit excessive intervention in the private sphere of citizens. Nevertheless, the implementation of complaint-based offenses in morality-related crimes presents a number of challenges. In practice, this mechanism may hinder victims’ access to justice due to various factors, including social pressure, stigma, unequal power relations, and economic dependence on the perpetrator. This study aims to comprehensively examine the concept of complaint-based offenses in morality crimes under the new Criminal Code and to analyze its implications for victim protection. This research employs a normative legal method using both statutory and conceptual approaches, supported by primary and secondary legal materials. The findings indicate that while complaint-based offenses provide victims with greater control over legal proceedings, they also pose risks of injustice, particularly for vulnerable groups such as women. Therefore, strengthening legal policies, improving victim assistance mechanisms, and adopting a more victim-oriented approach are essential to achieving substantive justice.